(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
From early adolescence to menopause, the menstrual cycle affects a woman’s physiological and psychological health for about 35 to 40 years in a normal population. Properly functioning hypothalamo pituitary ovarian axis, receptive endometrium with healthy ovum and sperm are considered to be the essential factors for conception. Acharyas have quoted Rutu, Kshetra, Ambhu and Beeja as Garbha sambhava samagri which is essential for conception where in Beeja can be taken as ovum. Shatapusha is mentioned in Kashyapa samhitha as Artavajanaka, hence an effort to evaluate its effect on estrous phase of female Wistar albino rats is the aim of this study. The selected animal was grouped into four groups with 6 animals each. The animal experiment showed significant increase in estrus phase of the oestrous cycle in rats which is the active phase of mating where the female receives the male.